Bis(propan-2-yl) [(1S)-1-(4-fluorophenyl)-1-hydroxy-2-nitroethyl]phosphonate - Mandal, T.; Samanta, S.; Broker, G.A.; Zhao, C.G.; Tiekink, E.R.T. (International Union of Crystallography, 2010)
In the title compound, C(14)H(21)FNO(6)P, a staggered conformation about the central P-C bond occurs, with the oxo and hydroxyl groups occupying diagonally opposite positions. The crystal structure features supramolecular chains mediated by O-H center dot center dot center dot O hydrogen bonds, which propagate in the a-axis direction. A C-H center dot center dot center dot O interaction consolidates the chains. Disorder was resolved for one of the isopropyl groups with a 0.60 (2):0.40 (2) occupancy ratio for the two components.